Antioxidant properties of Methanolic and Ethanolic extracts of Malaysian aromatic plants’ leaves: A comparative study - Abu Abas, Azlim Almey; Kamarudin, Kamarul Rahim; Mohamed Rehan, Aisyah; Jalal, K.C.A; Syed Osman Idid, Syed Zahir Idid; Mohamed Reyhan, Aisyah; Mustapha, Suleiman Koya (2008)
This study was done to determine the antioxidant properties of methanolic and ethanolic extracts of four Malaysian aromatic plants’ leaves, namely knotweed (Polygonum minus), curry (Murraya koenigii), kaffir lime (Citrus hysrix) and fragrant screwpine (Pandanus odorus). Total phenolic content (TPC) assay using Folin-Ciocalteu method was used to assess the amount of phenolic compounds in the extracts. Comparatively, methanolic extract of M. koenigii contained the highest phenolic content (8632 ± 42 mg/100g plant extract). Antioxidant activities in terms of total antioxidant and free radical scavenging activities of both methanolic and ethanolic extracts were measured by β-carotene bleaching assay and 2, 2’-diphenylpicrylhydrazyl (DPPH) radical scavenging activity assay, respectively. The methanolic extract of P. minus exhibited the highest total antioxidant activity (98%) while the ethanolic extract of P. minus indicated the highest free radical scavenging activity (IC50 = 1.19 mg/ml) as compared to the other samples. Furthermore, phytochemical analyses of the extracts were done by thin layer chromatography (TLC). Phenolic compounds were observed to be dominant in all extracts. Qualitative DPPH assay on TLC was also carried out to detect the antioxidant active compounds. The results showed that P. minus contained the highest number of active compounds. Most of the active compounds were very polar. Relatively, the current data suggested that of the four aromatic plants studied, P. minus and M. koenigii showed high potential as sources of natural antioxidant regardless whether they were extracted by methanol or ethanol.